Letter to Board of Trustees - Price, W.P.; Worley, J. (My University, 1879)
Letter from W.P. Price and J. Worley to Board of Trustees, Dahlonega, Georgia. January 1, 1879.
Letter from W.P. Price and J. Worley to Board of Trustees, Dahlonega, Georgia. January 1, 1879. 1 handwritten letter with seal. 1 page.
Keywords: Letters; Georgia; Records and correspondence; Georgia--Dahlonega